Reader habit, equipment and family income of the students of the UNAE - Castellano Gil, José (2021)
This study focuses on knowing the reader habit, equipment and family income of the student body of the National University of Education of Ecuador (UNAE). This work is part of a larger research project, whose main purpose is to contribute and analyze cultural indicators in the Ecuadorian university context, given the lack of data and studies. The methodology used is quantitative, descriptive and interpretative, based on the data collected in a survey applied to a population sample among the different careers and cycles offered by the UNAE, which amounts to 438 students and which has a degree of reliability 95% and an error of 5%. The main results obtained reflect the high level of appropriation of technological equipment, despite the fact that more than 80% of the students surveyed fit into the two most precarious quintiles of Ecuadorian society, and the strong influence exerted by the level of family income in the configuration of a certain pattern in the cultural consumption of the book. Other relevant features show a strong irruption of the digital world and an outstanding masculine participation in most of the acts related to the practice and reading habit